Membangun Guru Agama Katolik yang Kreatif, Inovatif, dan Motivatif di Masa Pandemi - Katarina Leba; Balthasar Watunglawar (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2022)
The purpose of this study is to describe and analyze the substantive perspectives of teacher creativity, innovation, and motivation as well as the characteristics of creative, innovative, and motivational Catholic teachers. This study uses a qualitative method. The data technique is done through literature review, observation, and documentation. Data were analyzed using descriptive qualitative. The results of the analysis were in the form of real conditions in the field which were obtained from opinions, including the perspective of the teaching of Jesus Christ. Perspective research was carried out by means of reflection, analysis, and comparison of each view and theory to find the advantages and disadvantages. Furthermore, it was drawn as the final report of this research. These results informed that creativity and intellectual initiative helped humans to solve research problems and answer goals. The power of innovation can be seen through the teacher's creations in making it easier for students to absorb the knowledge being taught. The teaching of Jesus is a major factor for creative, innovative, and motivational Catholic teachers. A creative, innovative, and motivational Catholic teacher must prioritize his essential duties; find students and answer their needs; using contextual media according to the needs of students or learners; always strives to be a person or a teacher with integrity, role model, and disregard.